Ground application of mating disruption against the gypsy moth (Lepidoptera: Erebidae). (6th September 2019) - Onufrieva, Ksenia S.; Hickman, Andrea D.; Leonard, Donna S.; Tobin, Patrick C.
Abstract: The gypsy moth, Lymantria dispar (L.) (Lepidoptera: Erebidae), is a non‐native defoliating insect that continues to expand its range in North America and undergo periodic outbreaks. In management efforts to suppress outbreaks, slow its spread and eradicate populations that arrive outside of the invaded range, aerial deployments of mating disruption tactics and pesticides are generally used. However, in some cases, such as in heavily urbanized areas or other landscapes where aerial deployments are not feasible or permitted, ground applications are required. Ground applications tend to be labour‐intensive to ensure adequate coverage. To better inform optimal deployment of ground applications of mating disruption, we measured the effectiveness of a pheromone formulation designed for ground application, SPLAT® GM, in forested areas of Virginia from 2011 to 2014 using different dosages and number of point applications. We observed that SPLAT® GM applied to the tree trunks at the dosages of 49.4 and 123.6 g AI/ha in 11 × 11 systematic grids (i.e., every 11 m) reduced male trap catch by >90% relative to untreated control plots, which based on previous studies corresponds to >95% reduction in gypsy moth mating success. Our observations suggest that ground applications of gypsy moth mating disruption can be a successful management tool when circumstances require it.